2015
DOI: 10.1309/ajcpab4a6wwpyien
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Quality Improvement in Tanzania

Abstract: The article describes the progress made in Tanzania's first cohorts, the obstacles encountered, and the lessons learned during the pilot and subsequent implementations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 14 publications
(18 reference statements)
1
25
0
3
Order By: Relevance
“…Laboratory results are perceived to be unreliable, especially when they are found to be discordant with clinical indications. 2 …”
Section: Introductionmentioning
confidence: 99%
“…Laboratory results are perceived to be unreliable, especially when they are found to be discordant with clinical indications. 2 …”
Section: Introductionmentioning
confidence: 99%
“…The study showed that the improvement plan consisted of formalized hands-on training under the Strengthening Laboratory Management Toward Accreditation program (SLMTA) that teaches the tasks and skills of laboratory management and provides the tools for implementation of best laboratory practice. (Andiric & Massambu, 2015).…”
Section: Results Of Literature Searchmentioning
confidence: 99%
“…Dez artigos identificaram impactos positivos (CHABANNON et al, 2012;GUINDO et al, 2012;CASTLE, 2012b;ABOU ELNOUR et al, 2014;AGHEORGHIESEI et al, 2014;GRATWOHL et al, 2014;GARG;NGUYEN, 2014;PARTHASARATHY;SUBRAMANIAN;QUAN, 2014;SISAY et al, 2015;TELEM et al, 2015). Por exemplo, foi observado um aumento significativo de 14% na sobrevida dos pacientes com leucemia crônica que receberam um transplante alogênico (transplante de células-tronco hematopoéticas) em um programa acreditado, em comparação com aqueles tratados em um programa não-acreditados (CHABANNON et al, 2012 (MCHUGH et al, 2013;CAUNDAY et al, 2013;CHUANG;HOWLEY;HANCOCK, 2013;DAY et al, 2013;DERIU et al, 2013;HOTCHKISS, 2014;LAFRANCE, 2014;MARONE et al, 2014;MARSHALL et al, 2014;MONTEIRO et al, 2014;RICCARDO;PARENT;DESALVO, 2014;THIELEN et al, 2014aTHIELEN et al, , 2014bMORAN, 2014;WALKER, 2014;WETTA et al, 2014;EL-JARDALI et al, 2014;EMER et al, 2014;HAGOS et al, 2014;ANDIRIC;MASSAMBU, 2015;TIMSINA, 2015;…”
Section: Análise De Conteúdounclassified
“…Em terceiro lugar, a introdução e utilização de indicadores (CAUNDAY et al, 2013;CHUANG;HOWLEY;HANCOCK, 2013;DERIU et al, 2013;HAGOS et al, 2014). Finalmente, os outros mecanismos identificados foram a abordagem de treinamento (DERIU et al, 2013;WETTA et al, 2014;ANDIRIC;MASSAMBU, 2015) e o apoio da liderança (MARONE et al, 2014;WETTA et al, 2014 (AMMAR et al, 2013;SALEH et al, 2013;KWON et al, 2013;MCHUGH et al, 2013;BEVC;SCHENCK, 2014;SONG;LI;ZHOU, 2014;WETTA et al, 2014;EL-JARDALI et al, 2014;EMER et al, 2014;LEE, 2014;MERKOW et al, 2014;MONTEIRO et al, 2014;WENSING, 2015;LIU et al, 2015). Os principais temas estão relacionados aos custos e despesas durante e após a acreditação.…”
Section: Análise De Conteúdounclassified
See 1 more Smart Citation